Permeation grouting diffusion mechanism of quick setting grout. (June 2022) - Zhang, Lianzhen; Yu, Rangang; Zhang, Qingsong; Liu, Rentai; Feng, Huijun; Chu, Yuntian
Highlights: Grouting model was developed considering nonuniform grout viscosity distribution. Quick setting property heavily affect permeation diffusion for fine sand. Nonuniform viscosity distribution is not negligible for grouting diffusion. Abstract: Quick setting grout is used in permeation grouting projects to control the grouting diffusion range effectively and reduce the waste of grout. Owing to the double-component injection method and quick setting property of the grout, the viscosity of the quick setting grout is non-uniformly distributed in the grouted region, which has a significant influence on the grouting diffusion process. In this study, the permeation grouting process of a quick setting grout was studied. A 2-D cylindrical permeation grouting diffusion model was developed considering the non-uniform distribution of grout viscosity. A visible permeation grouting diffusion simulation test system was designed and established. A series of tests were carried out to verify the correctness of the theoretical model, in which cement–sodium silicate grout, a typical quick setting grout, with two water–cement ratios (W/C = 1, 2) and gravel sand with two different ranges of particle size (2–5 mm, 5–20 mm) were used. The results show that (1) when the size of the void space in the sand stratum exceeds a certain value, the permeation diffusion of grout is completely controlled by grout gravity, and the influence of the quick setting characteristics can be ignored. Otherwise, the quick setting characteristics have the most important effect on permeation diffusion. (2) The calculated results agree well with the test results. The calculated injection pressure result is 1.0–1.4 times the experimental result, and the calculated diffusion radius is 95.7% –98.5% of the test value with the same final injection pressure. (3) It is necessary to consider the non-uniform distribution of viscosity in the calculation of the permeation grouting process of a quick setting grout. For a quick setting grout, if the non-uniform distribution of viscosity is not considered, the injection pressure would be overestimated by more than 10 times the actual value, and the diffusion radius would be underestimated by 30%–50% of the actual value.